2010
DOI: 10.1111/j.1758-2229.2010.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Syntrophic butyrate and propionate oxidation processes: from genomes to reaction mechanisms

Abstract: In anoxic environments such as swamps, rice fields and sludge digestors, syntrophic microbial communities are important for decomposition of organic matter to CO2 and CH4 . The most difficult step is the fermentative degradation of short-chain fatty acids such as propionate and butyrate. Conversion of these metabolites to acetate, CO2 , formate and hydrogen is endergonic under standard conditions and occurs only if methanogens keep the concentrations of these intermediate products low. Butyrate and propionate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(179 citation statements)
references
References 50 publications
(122 reference statements)
7
170
2
Order By: Relevance
“…Transformation of propionate into acetate and H 2 can only be realized via syntrophic metabolism under methanogenic condition (Stams and Plugge 2009). Some pure cultures including genera Pelotomaculum, Syntrophobacter, Smithella, and Desulfotomaculum are the hitherto identified propionate oxidizers (Muller et al 2010). In this study, a positive (p<0.05) corre lation between gen us Peloto maculum and Methanoculleus further suggested that the Pelotomaculum was likely to be involved in H 2 and acetate production.…”
Section: Discussionsupporting
confidence: 51%
“…Transformation of propionate into acetate and H 2 can only be realized via syntrophic metabolism under methanogenic condition (Stams and Plugge 2009). Some pure cultures including genera Pelotomaculum, Syntrophobacter, Smithella, and Desulfotomaculum are the hitherto identified propionate oxidizers (Muller et al 2010). In this study, a positive (p<0.05) corre lation between gen us Peloto maculum and Methanoculleus further suggested that the Pelotomaculum was likely to be involved in H 2 and acetate production.…”
Section: Discussionsupporting
confidence: 51%
“…The experimental results do not, however, conclusively prove this original hypothesis as the oxidation of propionic acid, with its uneven carbon chain length, produces a mixed product of acetate, CO 2 , H 2 and formate (Mueller et al, 2010), with side-reactions to produce butyrate and higher-chain fatty acids (de Bok et al, 2001;Stams et al, 1998). The enzymes required for propionic acid oxidation may themselves require the trace elements Se, Mo, and W (de Bok et al, 2003;Mueller et al, 2010;Worm et al, 2011). It has long been recognised, however, that the syntrophic degradation of propionate can be inhibited by a product-induced feedback inhibition (Dong, 1994;Fukuzaki et al, 1990;Kus and Wiesmann, 1995).…”
Section: 2mentioning
confidence: 52%
“…In Methanococcus vannielii, a single FDH was reported when cells were grown in the presence of tungsten, whereas two enzymes were observed in its absence (22). In Syntrophobacter fumaroxidans, a syntrophic acetogenic bacterium that can also grow by reduction of sulfate or fumarate, two W-containing FDHs have been isolated (12), and several others are encoded in the genome (32). In this organism, growth in the presence of W also leads to a strong increase in total FDH activity relative to growth with Mo, either during syntrophic growth with a methanogen or during growth with propionate and fumarate (35).…”
Section: Discussionmentioning
confidence: 99%